Calculation of Molar Volume of Mixtures of Krypton with Argon and Xenon from the Statistical-Mechanical Based Equation of State¦ - HAGHIGHI, BEHZAD; GHASEMI, HAMID; NIAFARI, MARYAM; MEHDI PAPARI, MOHAMMAD (Asian Journal of Chemistry, 2010)
In this paper, the analytical equation of state (EoS) proposed by Ihm-Song-Mason was applied to calculate molar volume of mixtures of krypton with argon and xenon. The pair interaction potential has been used to evaluate the second virial coefficients and the Ihm-Song- Mason equation of state (ISM-EoS) parameters (i.e., α and b). The calculated values of aforesaid quantities were applied to predict the molar volumes for mixtures of krypton with argon and xenon. Agreement with experiment was excellent for both systems.